Description of two new species of Odopoia Walker, 1871 (Hymenoptera: Chalcidoidea: Torymidae) from China, with a key to known species - Xiao, Hui; Jiao, Tianyang; Hu, Tingyu (Zootaxa, 2012)
The genus Odopoia Walker, 1871 is recorded from China for the first time and two new species, O. jianfengica Xiao etJiao sp. nov. and O. wenchangica Xiao et Hu sp. nov., are described and illustrated. The world species are differentiated in a key, the first for the genus.